FEATURES OF THE APPLICATION OF I-BEAMS WITH PERFORATED WEBS IN CONSTRUCTION - Godzynskyi, Ivan (Theory and practice of design, 2025)
Purpose. To investigate existing scientific sources concerning the stress–strain state of steel beams with perforated webs, their structural behavior, manufacturing features, hole dimensions, and the shapes of cutting lines. Methodology. The study employs a systematic approach that includes the analysis of scientific literature, generalization of experimental research results, numerical modeling, and comparative analysis. Results. Optimal hole sizes and shapes in the beam web have been identified to minimize the adverse effects on strength in weakened sections. The results of numerical modeling using the finite element method with plate elements show a high correlation with experimental data. Scientific novelty. The study summarizes and systematizes modern approaches to the design of steel I-beams with perforated webs, count the influence of hole shape, size, and arrangement on strength and stability. A distinctive feature of the work is the integration of experimental and numerical research results to determine the optimal geometric parameters of the perforation. Practical relevance. The findings can be applied in the design of steel structures with perforated elements, enabling more efficient use of materials without compromising load-bearing capacity. The proposed generalizations regarding the selection of hole shapes and configurations allow engineers to make more informed technical decisions during the design process. The practical relevance of the study is reinforced by its applicability in the context of Ukraine’s post-war reconstruction, where ensuring both reliability and cost-effectiveness of construction under resource constraints is critically important. The conclusions may be considered in the development of regulatory documents and guidelines for the use of perforated beam elements in construction.